Examination of the Relationship Between Students’ Science Achievements and Their Scientific Self-Concept by Using the Bootstrap Method - Miščević Kadijević, Gordana M.; Mandić, Danimir P. (Sociološki pregled, 2019)
This paper presents a specific research approach that should be used more frequently in the social sciences. The research problem concerned the relationship between two variables when a third one was included in the analysis and its influence on the initial variables removed. The subject of this research dealt with the relationship between students’ science achievements and their scientific self-concept when controlling the influence of the teachers’ assessment of the level of the research approach applied in their teaching. In order to examine this relationship, the research used country level data from a recently realized international study TIMSS in the fourth grade, and with the aim of obtaining the most reliable results, the bootstrap method was applied to generate confidence intervals for the correlations in question. It was found that the initial negative relationship was annulled by the inclusion of the third variable. The concluding remarks contain recommendations for improving domestic research practice.
Keywords: pedagogical research; bootstrap method; achievement; self-concept; TIMSS